2017
DOI: 10.24920/j1001-9242.2007.004
|View full text |Cite
|
Sign up to set email alerts
|

Value of Multi-detector CT in Detection of Isolated Spontaneous Superior Mesenteric Artery Dissection

Abstract: Objective To investigate the role of multi-detector computed tomography (CT) in the diagnosis and classification of isolated spontaneous superior mesenteric artery dissection (ISSMAD).Methods From July 2012 to December 2016, 30 consecutive patients with ISSMAD underwent CT scan at least two times. We retrospectively summarized the clinical characteristics and CT findings of them. The stenosis ratio of true lumen was compared between the patients without bowel ischemia and ones with bowel ischemia.Results There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 22 publications
0
19
0
1
Order By: Relevance
“…Therefore, CTA is currently the most sensitive and reliable method for diagnosing SISMAD. At our different hospitals, CTA is the diagnostic test of choice for patients suspected to have SISMAD, while CECT is the most commonly used test when SISMAD is diagnosed incidentally in China (5,6,17). However, in clinical practice, numerous patients cannot directly undergo CTA and rather undergo plain CT first.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, CTA is currently the most sensitive and reliable method for diagnosing SISMAD. At our different hospitals, CTA is the diagnostic test of choice for patients suspected to have SISMAD, while CECT is the most commonly used test when SISMAD is diagnosed incidentally in China (5,6,17). However, in clinical practice, numerous patients cannot directly undergo CTA and rather undergo plain CT first.…”
Section: Discussionmentioning
confidence: 99%
“…The specific etiology of SISMAD is unclear and multiple risk factors have been suggested to be related to this arteriopathy, including connective tissue diseases, cystic medial necrosis, arterial wall dysfunction involving atherosclerosis, fibromuscular dysplasia, vasculitis, tobacco use, atherosclerosis, segmental arterial mediolysis, alcohol abuse, obesity, heavy weight lifting, history of smoking or hypertension, pregnancy and hemodynamic forces caused by the convex curvature of the SMA (1,3,6,18,(20)(21)(22)(23)(24)(25). Patients with SISMAD were predominantly males with an average age of 55 years and this may be related to male smoking and drinking behaviors (6,17). Perhaps, SISMAD can be prevented by measures such as cessation of smoking and drinking alcohol and keeping good dietary habits (6,22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twentytwo 4,5,14-25,27-33 out of 30 studies (509 patients) reported bowel rest and fluid supplementation as a first approach, while strict blood pressure control using medications was performed in 296 (54.3%) patients. 4,[15][16][17][18][19][20][21][23][24][25]27,29,32,33,35 Anticoagulants were used in 20 studies 4,5, [14][15][16][18][19][20][21][22][23][24][25][26][27][29][30][31]34,35 with 451 (82.7%) patients. Data for conservative treatment with or without anticoagulants came from three studies 17,18,33 while two studies did not report the strict conservative treatment protocol.…”
Section: Conservative Treatmentmentioning
confidence: 99%
“…With the development of medical imaging, increasing cases of SISMAD are confirmed in patients with acute abdominal pain. At present, the diagnosis of SISMAD is mainly based on computed tomography angiography (CTA) or digital subtraction angiography (DSA) (4,5). Although CTA has served as an effective diagnostic tool for SISMAD, its application in clinical practice is limited by contrast agent allergy, overdose of radiation and high cost (6).…”
Section: Introductionmentioning
confidence: 99%